Arya Penangsang: Santri Kesayangan Sunan Kudus sebagai Pembangun Memori Kolektif dalam Revitalisasi Kota Cepu - Sukarjo Waluyo (UIN Sunan Gunung Djati Bandung, 2021)
The issue of locality emerged in line with the 1998 reform movement, one of which demanded decentralization of development, including culture. The local identity of the Cepu community is important in this study. Talking about Cepu City cannot be separated from the Islamic Sultanate of Demak, Sunan Kudus, and Arya Penangsang. Arya Penangsang is the grandson of Raden Patah (founder of the Islamic Sultanate of Demak), Sunan Kudus's favorite religious and intelligent student. He is also the Duke of Jipang (Cepu of the past) who is known to be wise, brave, and a staunch Muslim. However, Cepu is an old city that historically has always been defeated, especially after the collapse of the Islamic Sultanate of Demak which was replaced by Javanese rulers in Pajang and Mataram. In the coastal areas he was known as the prince of the last heir to the Islamic Sultanate of Demak who was killed dramatically. The representation of Cepu's local identity comes through the figure of Arya Penangsang and efforts to revitalize the past glory of Jipang Kadipaten as a means of articulation. Interestingly, Arya Penangsang is a figure whom the rulers and most of the Javanese people regard as an evil, cruel, and power-hungry rebel. Thus, efforts to represent the local identity of the Cepu community clash with the dominant discourse of Javanese society in general. Using the ethnographic method, this article aims to express the love of the Cepu people towards Arya Penangsang and the Kadipaten Jipang. The results of this study will explain how Arya Penangsang and the past glory of the Kadipaten Jipang have been awakened in the collective memory of the Cepu people. Arya Penangsang and the Kadipaten Jipang are currently constructed as local heroes in discourses on the revitalization of Cepu City. The results of this study contribute to become a model for the revitalization of other cities that have the same issue.